Study of the electrical conduction process in natural rubber-based conductive nanocomposites filled with cellulose nanowhiskers coated by polyaniline - Silva, Michael J. [UNESP]; Sanches, Alex O. [UNESP]; Cena, Cicero R.; Nagashima, Haroldo N. [UNESP]; Medeiros, Eliton S.; Malmonge, José A. [UNESP] (Wiley, 2021)
In the present work, the electrical properties of a natural rubber-based nanocomposite (NR) filled with cellulose nanowhiskers (CNW) coated with polyaniline (PANI) were studied. We developed a statistic model that simulates nanocomposite microstructure and conductivity, calculated using the transfer matrix technique. A two-dimensional network of resistors representing a microstructure of both the insulating region (NR) and conductive fillers (cellulose nanowhiskers coated with polyaniline - CNWP) was developed. The conductance of bond between two neighboring sites in the CNWP filler and two neighboring sites of the NR matrix was estimated using Drude's equation and Dyre's formula, respectively. Results of the simulations show that the conduction process between two sites of NR follows the modified Dyre model (RFEB), while between two CNWP sites follows the modified Drude model. The theoretical-experimental adjustment shows that the electrical conduction process occurs via hopping and tunneling between states located inside the CNWP phase, randomly distributed in the rubber matrix.
Keywords: cellulose nanowhiskers; conductive nanocomposite; natural rubber; polyaniline; statistic model